2014
DOI: 10.1590/so100-720320140005161
|View full text |Cite
|
Sign up to set email alerts
|

Maternal age and adverse perinatal outcomes in a birth cohort (BRISA) from a Northeastern Brazilian city

Abstract: The percentage of early teenage pregnancy (12-15 years old) was 2.2%, and of late (16-19 years old) was 16.4%, while pregnancy at an advanced maternal age (>35 years) was 5.9%. Multivariate analyses showed a statistically significant increase in preterm births among females aged 12-15 years old (OR=1.6; p=0.04) compared with those aged 20-35 years. There was also a higher rate in preterm births among females aged 16-19 years old (OR=1.3; p=0.01). Among those with advanced maternal age (>35 years old), the incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 26 publications
1
13
0
4
Order By: Relevance
“…However, in accordance with Vienne et al (2), these associations were not significant after adjusting for confounding variables. The results of studies related to the association of teenage pregnancy and IUGR are contradictory (11,12); in fact, some of them were not adjusted for confounding factors. We observed a lower incidence of intrauterine growth restriction in teenage pregnancy, especially in the older adolescent group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in accordance with Vienne et al (2), these associations were not significant after adjusting for confounding variables. The results of studies related to the association of teenage pregnancy and IUGR are contradictory (11,12); in fact, some of them were not adjusted for confounding factors. We observed a lower incidence of intrauterine growth restriction in teenage pregnancy, especially in the older adolescent group.…”
Section: Discussionmentioning
confidence: 99%
“…In low-and middle-income countries, pregnancy has been reported as the main factor of death in adolescent girls (1). Young maternal age has usually been considered a high risk in relation to adverse pregnancy outcomes (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Possible explanations for adverse pregnancy outcomes have been thought to be their biological immaturity or poor social, economic and behavioral factors such as smoking, alcohol/substance abuse, malnutrition and inadequate prenatal care (17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…9,10 For most authors, the definition of advanced maternal age (AMA) is 35 years and above. [11][12][13][14] However, in medical literature AMA is often defined as age over 40 years. 10,[15][16][17] Most studies conclude that pregnancy at advanced age is seldom without risks.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the status of advanced maternal age was 29.5%( 95%CI: 26.1%, 32.8%). This was higher than studies conducted in Israel (2.3% and 14%) [4,10], Malaysia (14.8%) [14], WHO Multicountry Survey (12.8%) [9], Northeastern Brazil (5.9%) [13], Nepal (4.53%) [15], South Africa (17.5%) [16], and United Kingdom (18.18%) [17]. However, it was lower than studies done in Iran (50.2%) [29], and Norway (33.4%) [11].…”
Section: Association Of Maternal Age With Adverse Obstetric Outcomesmentioning
confidence: 59%
“…In the last four decades, the rate of pregnancy in older women has increased [8]. Different studies which were conducted in Iran, Jerusalem, Israel; multi-country study; Norway; Asia; Muar district, Johor, Malaysia, Northeastern Brazilian city and cohort study in Israel showed that the incidence of pregnant women with advanced maternal age was 49.8%, 14%, 12.3%, 33.4%, 11.4-19.1%, 14.8%, 5.9% and 2.3% respectively [4,[9][10][11][12][13][14]. Similarly, other studies reported 4.53% from Nepal, 17.5% from South Africa, and 19.1% from the UK by North Western Perinatal Survey; which was a large contemporary cohort study [15][16][17].…”
Section: Introductionmentioning
confidence: 99%